Analysis of the Damage Mechanism Related to CO2 Laser Cochleostomy on Guinea Pig Cochlea - Xiang Liu; Xiao-qing Qian; Rui Ma; Fang-Lu Chi; Dong-Dong Ren (Neural Plasticity)
Different types of lasers have been used in inner ear surgery. Therefore, it is of the utmost importance to avoid damage to the inner ear (e.g., hyperthermia and acoustic effects) caused by the use of such lasers. The aim of this study was to use a high powered fibre-enabled CO2 laser (10 W, 606 J/cm2) to perform cochleostomies on guinea pig cochlea and to investigate the possible laser-induced damage mechanisms. The temperature changes in the round window membrane, auditory evoked brainstem response, and morphological of the hair cells were measured and recorded before and after laser application. All of the outcomes differed in comparison with the control group. A rise in temperature and subsequent increased hearing loss were observed in animals that underwent surgery with a 10 W CO2 laser. These findings correlated with increased injury to the cochlear ultrastructure and a higher positive expression of E-cadherin and β-catenin in the damaged organ of Corti. We assume that enhanced cell-cell adhesion and the activated β-catenin-related canonical Wnt-signalling pathway may play a role in the protection of the cochlea to prevent further damage.